Peran Hukum Adat Dalam Penyelesaian Kasus Kasus Kekerasan Terhadap Perempuan Di Kupang, Atambua,Dan Waingapu - Nurtjahyo, Lidwina; Nafi, Tien Handayani; Kusuma, Iva; Tirtawening, Tirtawening; Putra, Gratianus Prikasetya (UI Scholars Hub, 2016)
This paper describes the intervention of customary law in the resolution of cases of violence against women and children - especially the intervention that is considered to be able to give justice to the victims. Settlement cases selected by the families of the victims of the indigenous peoples are not limited to cases which are brought to the formal judicial forum. Non-formal mechanisms (through elders) often provide resolution forums. Kupang, Atambua, and Waingapu become the communities that still choose traditional institutions in resolving the case as option, including in resolving some cases of violence against women. Figures of violence against women in those areas are also quite high (in 2012 recorded 478 cases based on data from the National Commission on the Rights of Women and Children). This research is based on the perspective of socio-legal studies, especially the anthropology of law. Studying law with using interdisciplinary approaches, in order to enrich the legal studies with mainstream perspectives.